Pengaruh Real Time Interactivity dan Promotion Incentive Information terhadap Impulse Buying Behavior dengan Mediasi Perceived Trust Fashion di Live TikTok - Ricky Martin; Heriyadi; Bintoro Bagus Purmono; Wenny Pebrianti (PT. PENERBIT TIGA MUTIARA, 2025)
The growing dominance of impulse buying within TikTok's live streaming commerce, particularly in the Fashion product segment, signifies a transformation in digital consumer behavior influenced by the dynamics of real-time interactivity and incentive-based promotional strategies. This study empirically examines the effects of real-time interactivity and promotion incentive information on impulse buying behavior, with perceived trust serving as a mediating variable that explains the psychological pathway between digital stimuli and spontaneous purchase decisions. Employing a quantitative approach with an associative causal design, data were collected from 231 active TikTok users in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) version 4.0. The analysis reveals that both exogenous variables significantly enhance the tendency for impulsive purchases, both directly and indirectly through the mediation of perceived trust. Responsive real-time interactions and exclusive, time-sensitive promotions effectively foster consumer trust in sellers, which subsequently accelerates unplanned buying behavior. These findings advance theoretical discourse in digital marketing literature by emphasizing the critical integration of interactivity, promotional stimuli, and affective trust mechanisms in shaping purchasing decisions within persuasive and simultaneous digital environments. The practical implications of this study offer strategic insights for businesses, encouraging the optimization of interactive features and promotional tactics to establish credibility and drive instant sales conversions in the context of e-commerce live streaming.